'A chronology of some Memorable Accidents': the representation of the recent past in English almanacs, 1648–60. Issue 255 (17th January 2019) - Peck, Imogen
Abstract: This article explores the ways the political upheavals of the mid seventeenth century were represented in English almanacs, and argues that study of this much overlooked printed product illuminates several facets of the mental afterlife of Britain's domestic conflicts. It contends that the prominence of political and military events from the sixteen-forties and-fifties within almanacs shows a popular demand for material that helped people remember the events of the bloody recent past and that these recollections served a range of purposes, from prognostic input to aide memoire. In addition, it suggests that the language in which the recent past was presented – primarily by almanac compilers but also by their readers – is revealing of the ways these events were interpreted and memorialized, and of some of the contests over recent memory that operated in mid seventeenth-century England.